Endovascular therapy for vasospasm after aneurysmatic subarachnoid hemorrhage. (2nd September 2016) - Kerz, Thomas; Boor, Stephan; Ulrich, Anna; Beyer, Christian; Hechtner, Marlene; Mueller-Forell, Wibke
Abstract: Introduction: Balloon angioplasty and/or selective intra-arterial vasodilator therapies are treatment options in patients with vasospasm after subarachnoid hemorrhage (SAH). We analyzed the effect of balloon angioplasty and/or selective intra-arterial vasodilator therapy in our patients. Methods: Twenty-six patients (vasodilation group, VDT) were treated with intra-arterial nimodipine. The balloon angioplasty with nimodiopine-group (BAP-N group) comprised 21 patients. The primary endpoint of this study was successful angiographic vessel dilation in vasospastic vessels after balloon angioplasty, together with nimodipine (BAP-N group), compared to intra-arterial vasodilator therapy (VDT group) with nimodipine alone. Results: A significant effect of angioplasty plus nimodipine was found in the central arteries (composite endpoint) with an OR of 2.4 (95% CI: 1.4–4.2], p  = 0.002), indicating a chance of improvement of the BAP-N group of more than twice compared to nimodipine infusions alone. Significant advantages for BAP-N-therapy were also encountered in the internal carotid artery (OR 5.4, p  < 0.001) and basilar artery (OR 29.7, p  = 0.003). A joint analysis of all arteries combined failed to show significant benefit of BAP-N therapy (OR 1.5, p  = 0.079), which was also true for cerebral peripheral arteries (OR 0.77, p  = 0.367). There was no difference in clinical outcome between both groups. Conclusions: In SAH patients with vasospasm, a combination therapy of balloon angioplasty and intra-arterial nimodipine resulted in a more than doubled vasodilative effect in the central cerebral arteries compared to the sole infusion of nimodipine. Regarding the ICA and BA arteries, this beneficial effect was even more pronounced. Although there was a tendency of better effects of the BAP-N group, regarding the overall effect in all territories combined, this failed to reach statistical evidence. In cerebral peripheral arteries, no differences were observed, and there was no difference in clinical outcome, too.